Consumer Behavior: The Psychology of Marketing - Mykhailyk, Natalia (My University, 2014)
There are several units in the market that can be analyzed but the most important one is the consumer. However, there is also a need to analyze one’s own firm’s strengths and weaknesses and those of competing firms. To assess a competing firm’s potential threat, we need to examine its assets (e g., technology, patents, market knowledge, awareness of its brands) against pressures it faces from the market. Finally, we need to assess conditions (the marketing environment). For example, although we may have developed a product that offers great appeal for consumers, a recession may cut demand dramatically.
Keywords: consumer; marketing; споживач; маркетинг; потребитель